Principal component analysis of morphometric traits in Katjang, Boer, and their crosses goats - Hifzan, R. M.; Mamat-Hamidi, K.; Bugiwati, S. R. A.; Dagong, M. I. A.; Nur Aida, M. T.; Salisi, M. S.; Hafiz, A. W. M.; Izuan Bahtiar, A. J.; Nurulhuda, M. O.; Ainu Husna, M. S. S.; Muhammad, M. S. (Diponegoro University, 2025)
Principal component analysis (PCA) is commonly used to examine the relationship among mor-phometric traits and determine which traits effectively describe the body conformation. This study evaluated the morphometric traits of Katjang, Boer, and Katjang × Boer goats through PCA to identify key indicators of body conformation and productivity. A total of 375 does (100 Katjang, 153 Boer, 122 Katjang x Boer) aged 1.5–2 years were measured for body weight (BW), body length (BL), chest depth (CD), chest girth (CG), height at withers (HW), width at withers (WW), hip height (HH), and rump width (RW) raised under semi-intensive management at MARDI Kluang, Malaysia. Results revealed significant (P < 0.05) interbreed differences, with Boer does exhibiting superior size (BW: 39.95 ± 2.22 kg; CG: 80.77 ± 3.96 cm) and Katjang x Boer does showing intermediate values (BW: 32.35 ± 2.65 kg; CG: 70.10 ± 1.63), reflecting heterosis effects. PCA identified two principal components (PCs), with PC1 (57.8–64.0% variance) strongly correlated with CG (0.89–0.94), BW (0.85–0.90), and BL (0.80–0.85), while PC2 (16.0–17.8% variance) distinguished taller/narrower (positive HH/HW loadings) from shorter/wider conformations (negative RW/WW loadings). Boer goats had the highest PC1 eigen-value (5.12), confirming their robust frame. Chest girth emerged as the most reliable predictor of BW (r = 0.85–0.89, P < 0.01), supported by high communality values (0.81–0.89). Body index classifica-tion placed Katjang in the brevigline group (BI: 81.45 ± 2.34) while Boer and Katjang x Boer does in medioline (BI: 85.12–86.51), aligning with their meat production potential. These findings underscore CG utility in selection programs and highlight the conserved morphological integration across breeds, offering practical benchmarks for genetic improvement under Malaysian climate.